Syzygium cumini (L.) Skeels extracts; in vivo anti-nociceptive, anti-inflammatory, acute and subacute toxicity assessment. (6th April 2022) - Qamar, Muhammad; Akhtar, Saeed; Ismail, Tariq; Wahid, Muqeet; Ali, Sajed; Nazir, Yasir; Murtaza, Shahid; Abbas, Malik Waseem; Ziora, Zyta M.
Abstract: Ethnopharmacological relevance: Syzygium cumini (L.) Skeels has been extensively used in the ancient medical system of Pakistan, India, Bangladesh, and Sri Lanka to combat diabetes, inflammation, and renal disorders. These health-promoting aspects of S. cumini are related to bioactive metabolites such as phenolic acids, anthocyanins, tannins, and flavonoids. Aim of the study: Earlier to this study, we have reported S. cumini extracts as potential sources of bioactive compounds bearing antioxidant and anti-inflammatory properties. However, prior further suggesting S. cumini fruit extracts for consumption against inflammatory disorders, it was mandatory to validate the claim and explore toxicity of the extracts. This study aims to determine the in vivo anti-nociceptive, anti-inflammatory, acute, and subacute toxicity properties of S. cumini crude extracts, followed by identifying and quantifying bioactive metabolites. Material and methods: In the present study, the anti-nociceptive and anti-inflammatory potential of S. cumini sequential crude extracts were evaluated using formalin and glutamate-induced paw licking method in mice. The acute and sub-acute toxicity assessment of active extract was performed by oral administration in rats. An acute toxicity trial was performed with two different doses, i.e., 2000 mg/kg and 3000 mg/kg for consecutive 14 days, whereas a sub-acute toxicity study was conducted at doses of 750 mg/kg and 1500 mg/kg for the next 28 days. Identification of bioactive compounds was performed using HPLC, and at the end, in silico docking calculations of identified compounds were performed. Results: The 100% methanolic extract (SCME) protected the mice from painful stimulation of formalin and glutamate in a dose-dependent manner with the maximum effect of 49% and 67% at 200 mg/kg, respectively, followed by moderate and non-influential effects of 50% methanolic extract and dichloromethane (DCM) extracts when compared to control, i.e., normal saline. The results of acute toxicity recorded LD50 of SCME over 3000 mg/kg, and no antagonistic effects were recorded during the subacute study when SCME dispensed at the rate of 750 mg/kg and 1500 mg/kg. SCME was found to induce no adverse effects to kidney, heart, liver, spleen, and paired lungs examined by hematological, serum biochemical, histological analysis. HPLC analysis of S. cumini 100% methanolic extracts revealed the presence of delphinidin 3-glucoside, peonidin-3, 5-diglucoside, scopoletin, and umbelliferone at the concentration of 127.4, 2104, 31.3, 10.4 μg/g whereas in 50% methanolic extract, the quinic acid, catechin, and myricetin were present at the concentration of 54.9, 63.7, 12.3 μg/g, respectively. Umbelliferone and scopoletin are newly reported compounds in the present study. In silico docking calculations of these compounds indicated the potential of anti-nociceptive and anti-inflammatory activities. Conclusions: These findings validate that S. cumini fruit extracts are a rich source of bioactive compounds that needs to be considered to enhance biological activities with lesser side effects. Graphical abstract: Image 1